![\frac{4}{3} x + \frac{5}{2} = \frac{ - 3}{2} + x \frac{4}{3} x + \frac{5}{2} = \frac{ - 3}{2} + x](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B3%7D+x+%2B++%5Cfrac%7B5%7D%7B2%7D++%3D++%5Cfrac%7B+-+3%7D%7B2%7D++%2B+x)
solve for x:
Answers
Answered by
1
Answer:
4x/3-x = -3/2-5/2
x = -8/2
x = -4
Step-by-step explanation:
hope this helps u
pls mark me the brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d16/d771ac254619e6ba7bff3a74568397af.jpg)
Similar questions
History,
1 month ago
History,
1 month ago
Science,
1 month ago
Social Sciences,
3 months ago
Social Sciences,
3 months ago
Biology,
11 months ago
Math,
11 months ago